Fulminant emphysematous pyelonephritis in a transplant kidney (clinical observation and literature review) - R. N. Trushkin; S. S. Andreev; N. I. Belavina; T. K. Isaev; D. E. Okonskaya; E. S. Stolyarevich; N. N. Klochkova; M. A. Lysenko (Вестник трансплантологии и искусственных органов, 2025)
Emphysematous pyelonephritis (EPN) is a necrotizing infection of the renal parenchyma and its surrounding areas that causes gas accumulation around the renal parenchyma, collecting system and surrounding tissues in the process of vital activity of several microorganisms. EPN occurs nearly exclusively in people with diabetes. Treatment strategies for EPN have evolved over the past 20 years, with minimally invasive procedures replacing nephrectomy, which has resulted in lower mortality rates (12.5–13%). EPN is rare in kidney transplant (KT) recipients and is characterized by a severe, often fulminant course with a high rate of adverse outcomes, which is determined primarily by background immunosuppressive therapy. There is no universally accepted consensus on the radiographic classification of EPN in KT recipients and its management. We present the first description of EPN in transplanted kidney in a 45-year-old woman with post-transplant diabetes, obesity and recurrent urinary tract infections. Massive antibiotic therapy (ABT), percutaneous nephrostomy, transplantectomy, renal replacement therapy, selective cytokine adsorption, and ventilatory support were all administered on the patient after she was admitted to the hospital with increasing clinical symptoms of sepsis and multiple organ failure. Death occurred on the fourth day after disease onset. The article examines 38 clinical cases from the English-language segment of the medical literature from the late 1970s to the present. EPN in KT recipients is characterized by the predominance of male gender, including among the deceased, rapid development of sepsis and acute kidney injury. There was no statistically significant difference in the frequency of emergency transplantectomies among surviving and deceased patients. Mortality was 28%. The issue of EPN in transplanted kidney requires more research and the development of optimal therapeutic plans, including surgical strategies.